PERBANDINGAN HASIL PENETAPAN PARAMETER SPESIFIK DAN NON-SPESIFIK ANTARA SIMPLISIA TERHADAP EKSTRAK METANOL PURUN TIKUS (Eleocharis Dulcis) - Didik Rio Pambudi; Eka Fitri Susiani; Ria Hervina Sari; Noor Rahmah; Cast Torizellia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Eleocharis dulcis is a swamp plant has potential as a traditional medicine. The purpose of this study was to compare the results of determining specific and non-specific parameters on simplicia and methanol extract of purun tikus’s stems. Determination of specific parameters includes organoleptic, macroscopic - microscopic tests, water soluble extract content, ethanol soluble extract content and phytochemical screening such as testing for alkaloids, flavonoids, tannins, saponins and steroids/triterpenoids. Determination of non-specific parameters includes drying shrinkage, determination of total ash content, acid insoluble ash content and heavy metal contamination. The results of the study on the specific parameters of stem extract showed that the simplicia powder was light brown in color, had a characteristic odor that was not pungent and had a bitter taste and on microscopic examination only the simplicia could be observed epidermis, transport bundles, parenchyma and collenchyma fragments,. The results of the non-specific simplicia characterization test showed drying shrinkage of 8.91%, total ash content of 13.79%, acid insoluble ash content of 6.89%. The results showed that both simplicia and methanol extract of purun tikus’s stems met the general requirements for specific and non-specific characteristics except for the total ash content of the simplicia which was declared not eligible.